Corruption as a Social Phenomenon: Philosophical Analysis - Peniaz, Pavlo; Guessab, Karim El; Bilokopytova, Nina (Вісник гуманітарних наук, 2025)
The article is devoted to the generalization of knowledge on the social phenomenon of corruption. The scientific approaches were analyzed in the study of the social phenomenon of corruption. The essence and content of this concept are clarified. The theoretical basis of the study was the works of N. Machiavelli, T. Hobbes, M. Weber, J.-C. Wake, E. Cassirer, M. Foucault, P. Berger and T. Luckmann and others. It was considered following political, legal, socio-economic and psychological approaches to the study, which confirmed the interdisciplinary nature of the studied phenomenon. It was also paid attention to such ethical categories as: goals, motives, values, attitudes of employees. The methodological basis was applied historical, socio-philosophical analysis, content analysis of publications in scientific publications and periodicals, the principle of systematicity, analysis and synthesis. It was sharpened attention on traditional, «idealistic philosophical», «revisionistical» and «Marxist» approaches. The purpose of the study was to carry out a substantive analysis of the social phenomenon of corruption. Representation of the interpenetration and synergy of different sciences (disciplines) on corruption, using an interdisciplinary approach. Development of recommendations for using an approach that involves strengthening interaction and mutual enrichment of tools for obtaining new scientific knowledge. Also was given examples of anti-corruption strategies in some countries (Singapore, USA, Germany, Egypt, UAE). As a conclusion, it was noted that most researchers consider corruption to be a source of disorganization, «pathology of society». At the same time, just a few of research pay attention to the dynamics of this social phenomenon, taking only how corruption becomes a problem in the eyes of society. Finally, let us recall that corruption is also a tool capable of providing vertical mobility to those social groups, or rather, their representatives, for whom other opportunities are closed.